Modulation of phosphatase of regenerating liver-1 within placental mesenchymal stem cells instigates the transition between epithelial-to-mesenchymal transition and mesenchymal-to-epithelial transition subsequent to hepatic fibrosis - Jae Yeon Kim; Hyeri Park; Soo Young Park; Se Ho Kim; Ja Yun Lim; Ki Seog Lee; Si Hyun Bae; Gi Jin Kim (Clinical and Molecular Hepatology, 2025)
Background/Aims Epithelial-to-mesenchymal transition (EMT) plays a crucial role in hepatic fibrogenesis and liver repair in chronic liver disease. Our research highlights the antifibrotic potential of placenta-derived mesenchymal stem cells (PD-MSCs) and the role of phosphatase of regenerating liver-1 (PRL-1) in promoting liver regeneration. Methods We evaluated the efficacy of PD-MSCs overexpressing PRL-1 (PD-MSCsPRL-1) in a bile duct ligationinduced rat injury model, focusing on their ability to regulate EMT. Results PD-MSCsPRL-1 significantly reduced mesenchymal markers by downregulating TGFB1/SMAD2, outperforming naïve PD-MSCs. The transplantation of PD-MSCsPRL-1 enhanced BMP7/SMAD1/5 expression, promoting epithelial marker expression and stimulating BMP7 within hepatocytes, modulating downstream SMAD signaling. Importantly, further validation confirmed that PRL-1 directly interacts with BMP7 in hepatocytes. Conclusions PRL-1 expression in PD-MSCsPRL-1 restores TGFB1/BMP7 balance, promoting hepatic regeneration through mesenchymal-to-epithelial transition. These findings highlight the therapeutic potential of engineered MSCs for liver disease and suggest innovative strategies for future stem cell therapies.